Immunogenicity and safety of the AS04-HPV-16/18 and HPV-6/11/16/18 human papillomavirus vaccines in asymptomatic young women living with HIV aged 15–25 years: A phase IV randomized comparative study. (June 2020) - Folschweiller, Nicolas; Teixeira, Julio; Joshi, Smita; Goldani, Luciano Z; Supparatpinyo, Khuanchai; Basu, Partha; Chotpitayasunondh, Tawee; Chetchotisakd, Ploenchan; Ruxrungtham, Kiat; Roteli-Martins, Cecilia; Grinsztejn, Beatriz; Quintana, Silvana Maria; et al.
Abstract: Background: Women living with HIV (WLWH) are at higher risk of acquisition and progression of human papillomavirus (HPV) infection. Evidence on effect of HPV vaccination in this population is limited. Methods: This phase IV randomized controlled observer-blind study assessed immunogenicity and safety of two HPV vaccines (AS04-HPV-16/18 vs. 4vHPV) given in WLWH (stage 1) and HIV- females aged 15–25 years. Co-primary endpoints were to demonstrate, in WLWH subjects, non-inferiority (and if demonstrated, superiority) of AS04-HPV-16/18 vs. 4vHPV for HPV-16 and HPV-18 by pseudovirion-based neutralization assay (PBNA) at month 7 and safety. Non-inferiority criteria was lower limit (LL) of the 95% confidence interval (CI) of the GMT ratio AS04-HPV-16/18/4vHPV above 0.5, in the according to protocol population. NCT01031069 Findings: Among 873 subjects recruited between 26-Oct-2010 and 14-May-2015, 546 were randomized (1:1) and received at least one vaccine dose (total vaccinated cohort, TVC): 257 were WLWH (129 AS04-HPV-16/18; 128 4vHPV) and 289 were subjects without HIV (144 AS04-HPV-16/18; 145 4vHPV). Baseline CD4 cell count in WLWH was at least 350 cells/mm 3 . At month 7, AS04-HPV-16/18 showed immunological superiority to 4vHPV in WLWH. Neutralizing anti-HPV-16 and HPV-18 antibody GMTs were 2·74 (95% CI: 1·83; 4·11) and 7·44 (95% CI: 4·79; 11·54) fold higher in AS04-HPV-16/18 vs. 4vHPV (LL of the GMT ratio >1 in TVC, p <0·0001), respectively. Similar results were observed by ELISA up to month 24. Solicited local and general symptoms were in line with product labels. The number of reported serious adverse events (SAEs) was balanced throughout the study. Interpretation: Both vaccines showed an acceptable safety profile in all subjects. Despite the absence of an immunological correlate of protection for HPV, differences in immune responses elicited by the vaccines especially for HPV-18 may translate into longer lasting or more robust protection against cervical cancer with the AS04-HPV-16/18 vaccine in WLWH. Funding: GlaxoSmithKline Biologicals S.A. funded this study (NCT01031069) and related publications. Trial registration: www.clinicaltrials.gov - NCT01031069